1818 (H. 1233) TARİHLİ BALAT ŞER'İYYE SİCİLİ (METİN DEĞERLENDİRME VARAK 1-14) - MENGİRKAON, SABRİ (Fırat Üniveristesi, 2014)
Şer'iyye sicilleri ihtiva ettikleri belge ve bilgiler nedeniyle bulundukları bölge ve yazıldıkları dönemle ilgili çeşitli ve çok zengin bilgiler içermektedirler. 130 numaralı Balat şer'iyye sicili bize Balat ile ilgili sosyal ve coğrafi alanlarda çeşitli bilgiler sunmaktadır. Bu sayede bizler sicilin yazıldığı dönemdeki sosyal yapı ve mahalli yapılar hakkında bilgiler edinebilmekteyiz. 130 numaralı Balat şer'iyye sicili bize 1818(H.1233) tarihindeki İstanbul'da ki sosyal yapı ve iktisadi uğraşlar hakkında bilgiler sağlayacak ve özellikle şehir tarihçileri tarafından istifade edilebilecektir. Adı geçen sicilde daha çok evlilik, boşanma, alım-satım, tereke ve vasi tayini ile ilgili belgeler bulunmaktadır. Anahtar Kelimeler: Osmanlı, Şer'iyye Sicilleri, Şer' i Hukuk, Sicil, Balat, Balat Sicilleri.

Because şer'iyye registers contain documents and informations, they cover various and valuable information about the place and the period in which they were written. Number 130 Balat şer'iyye register serves up various information about social regulation and geographical data of Balat. Thus, we are able to understand a lof of valuable information about social regulation and geographical data of the Balat and İstanbul, the capital of the Ottoman Empire. Number 130 Balat şer'iyye register provides us with understanding of the social situation of İstanbul and the economical properties of the city in 1818 (Muslim Calendar 1233), and they will be made use of by city historians. The register in question especially covers marriage, divorce, purchase- sell, estate and conservator letters. Key Words: Ottoman, Court records register, Register, Balat Court Records Registers.
Balat court records register dated on 1818 (h. 1233) (text assessment pages 1-14)
Keywords: Tarih